Promovendo matéria escura leve em cosmologia não-padrão - Oliveira, Vinícius Luiz Barbosa (2021)
Dark Matter (DM) is one of the main enigmas of our time. Evidence of its existence in our universe has been observed for decades and there are several theories that try to explain it. The one that assumes DM being composed of particles is the one that currently has the greatest credibility in agreeing with the experimental bounds. However, the Standard Model of Particle (SM) does not have any candidate that satisfies the characteristics of DM, which are: being stable, electrically neutral, cold or warm and non-baryonic. Given the above, the need arose to go beyond the SM and extend it. There are several SM extensions can provide DM candidates with different properties (mass and interactions). However, the class of WIMPs triumphed as candidates for DM, since they respect experimental bounds while their interaction is of order of the electroweak, which make them experimentally accessible. It is noteworthy that the fact that WIMPs interact weakly requires them to be heavy, with mass grossly greater than O(10 GeV), in order to be sufficiently abundant. However, despite the success of WIMPs, so far no signs of these particles have been found in the experiments, and more recent works has shown that cold dark matter, such as WIMPs, can negatively affect the period of structure formation. As a possible solution to the WIMPs problem, we will, in this dissertation, present a mechanism that enables the existence of light dark matter, with mass O(2 keV). An DM with this mass tends to be naturally hot and over-produced, when produced via freeze-out, not respecting the experimental bounds. However, we will demonstrate that if the early universe was dominated by an period of matter followed by a considerable increase in entropy, then light DM has its abundance diluted and becomes warm. Additionally, we will show evidence that this type of DM can solve the problems in the period of structure formation related to cold DM. Finally, we will apply such a mechanism to an extension of SM in which the lighter right-hand neutrino is the dark matter candidate.